Global transformer design optimization using deterministic and non-deterministic algorithms - Amoiralis, E. I.; Tsili, M. A.; Kladas, A. G. (2012 XXth International Conference on Electrical Machines, 2012)
The present paper compares the application of one deterministic and three non-deterministic optimization algorithms to global transformer design optimization. One deterministic optimization algorithm (Mixed Integer Nonlinear Programming), is compared to three non-deterministic approaches (Harmony Search, Differential Evolution and Genetic Algorithm). The comparison yields significant conclusions on the efficiency of the algorithms and the selection of the most suitable for the transformer design optimization problem.